BSCI-19. EFFECT OF STEREOTACTIC RADIOSURGERY ON NON-SMALL CELL LUNG CANCER BRAIN METASTASIS: CORRELATIVE RADIOBIOLOGIC ANALYSIS FROM PHASE-II CLINICAL TRIAL NCT03398694. (12th August 2019) - Huff, Wei; Shireman, Jack; Monaco, Gina; Agrawal, Namita; Park, Cheol; Saathoff, Miranda; Henriquez, Mario; Watson, Gordon; Ahmed, Atique; Dey, Mahua
Abstract: BACKGROUND: Stereotactic radiosurgery (SRS) is an increasingly common modality used with or without surgery for brain metastases (BM). However, biological effect of SRS to tumors in vivois not known. METHODS: Patients were treated with SRS prior to surgery as per the clinical trial protocol. The resected tumor was divided into two groups: 'center' and 'periphery' with respect to the center of SRS treatment with periphery within 50%-isodose-line. Tissue was analyzed by whole exome sequencing (WES) and compared between the two groups as well as to non-radiated control tissues. RESULTS: All sequenced samples contained greater than 95% clean reads with an average read density of 100 base pairs and mapping efficiency of >99%. Preliminary analysis focused on SNP and Indel detection. In pooled groups with n=7 replicates there was no statistically significant differences in total mutation burden in either SNP's or Indels compared between controls and both treatment locations. Delving deeper intronic, frameshift, missense, and nonsense mutations all also showed insignificant changes between controls and center or peripheral tumor locations (p >0.5, p >0.1, p >0.4, p >0.3 respectively) hinting that at a pooled biological level there are not significant mutational burdens between treatment locations. However, at the individual level, matched comparison of SRS samples originating from the center or periphery of the same tumor showed total mutational burden differences. 6 out of 7 (86%) patients showed decreased total number of indels in peripheral vs. center and 5 out of 7 (71%) patients showed decreased number of SNP's in peripheral vs. center locations. CONCLUSION: Ultimately, these data demonstrate the power of matched patient controls over bulk analysis in order to elucidate smaller but possibly biologically meaningful effects, and point to a possible location dependency in treatment associated mutation burden within a single patient and single tumor that may be masked at a population level.